Hedging long-dated interest rate derivatives for Australian pension funds and life insurers - Fergusson, Kevin; Platen, E. (Institute of Actuaries of Australia, 2014)
Many pension funds and life insurers seek to hedge their exposure to low interest rates using long-dated interest rate derivatives. This paper extends an approach of Platen and Heath 2006 to price and hedge long-dated interest rate derivatives using a combination of Australian cash, bonds and equities and under a variety of market models. The results show the models under which the lowest cost hedge is achieved.